The functional outcomes of stroke patients who are HIV positive, HIV negative and HIV undiagnosed, following rehabilitation: a descriptive study - Hartley, Tasneem (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScPhysio)--Stellenbosch University, 2017.